Peningkatan pengetahuan pencegahan anemia pada remaja 8000 HPK dan pemberian ketrampilan pengolahan abon telur pada kader di Desa Bontomanai, Jeneponto - Triananinsi, Nurhidayat; Khatimah, Husnul; Supardi, Nurjannah; Wahyuni, Wahyuni (JOURNAL OF Public Health Concerns, 2025)
Background: The 8000 First Days of Life program is a systematic intervention in three phases of life after 1000 First Days of Life, namely the phase at the age of 5-9 years, where in this phase the incidence of infectious diseases and malnutrition are the main problems that interfere with growth and development. The prevalence of stunting in Jeneponto Regency reached 39.8%, far above the national average (21.6%), with anemia in adolescents as one of the causative factors. Observations at the Bontomanai Village Posyandu showed that most adolescents were not aware of the importance of consuming iron tablets, with 4 out of 6 adolescents showing signs of anemia. In addition, there is no place for consultation and health education for adolescents in this area. Purpose: To increase knowledge about anemia prevention and the skills of Posyandu cadres through counseling and training in food processing as support for nutritional adequacy. Method: The activity was carried out on September 18, 2024 at the house of the head of Bontomanai Village, Jeneponto Regency. The activity was attended by 32 cadres and 5 adolescent girls. The target of this community service activity is focused on the cadres of the Bontomanai Village Posyandu work area, Rumbia District, Jeneponto Regency. Delivering material using lecture and discussion methods regarding anemia, causes, symptoms, long-term impacts, and management and prevention of anemia. Simulations are provided in the form of demonstrations and assistance regarding the procedure for processing eggs into shredded meat. The questionnaire data is tabulated and then analyzed by comparing the results of the accumulated pre-test scores with the post-test scores accompanied by direct observation notes when providing assistance. Results: There was an increase in the number of participants who had knowledge about anemia in the good category from before the counseling as many as 5 people (13.5%) to 20 people (54.1%). There was also an increase in the number of participants who had skills in processing eggs into shredded meat from before the counseling as many as 10 people (27.0%) to 20 people (94.6%). Conclusion: Counseling activities to increase knowledge about anemia by providing skills in the form of food processing skills have a very positive influence on increasing the understanding of cadres in efforts to prevent anemia and stunting. Suggestion: Cadres can continue this activity together with partners and coordinate with the PKM team in a joint effort to prevent anemia in 8000 First Days of Life and stunting. Keywords: Adolescent girls; Anemia; Fulfillment of nutrition; Posyandu cadres; Skills                                                                                                                                                        Pendahuluan: Program 8000 HPK merupakan sebuah intervensi yang sistematis pada tiga fase kehidupan setelah 1000 HPK, yaitu fase pada usia 5-9 tahun, dimana pada fase ini kejadian penyakit infeksi dan kekurangan gizi menjadi masalah utama yang mengganggu tumbuh kembang. Prevalensi stunting di Kabupaten Jeneponto mencapai 39.8%, jauh di atas rata-rata nasional (21.6%), dengan anemia pada remaja sebagai salah satu faktor penyebab. Observasi di Posyandu Desa Bontomanai menunjukkan bahwa sebagian besar remaja tidak menyadari pentingnya konsumsi tablet tambah darah, dengan 4 dari 6 remaja menunjukkan tanda anemia. Selain itu, belum tersedia tempat konsultasi dan wadah edukasi kesehatan untuk remaja di wilayah ini. Tujuan: Untuk meningkatkan pengetahuan tentang pencegahan anemia dan keterampilan kader posyandu melalui penyuluhan dan pelatihan pengolahan makanan sebagai dukungan kecukupan gizi. Metode: Kegiatan dilakukan pada tanggal 18 September 2024 di rumah kepala Desa Bontomanai Kabupaten Jeneponto. Kegiatan dihadiri oleh 32 kader dan 5 remaja putri. Sasaran kegiatan pengabdian kepada masyarakat ini di fokuskan pada para kader wilayah kerja posyandu Desa Bontomanai Kec. Rumbia Kab. Jeneponto. Menyampaikan materi menggunakan metode ceramah dan diskusi mengenai anemia, penyebab, gejala, dampak jangka panjang serta penanggulangan dan pencegahan anemia. Diberikan simulasi dengan berupa peragaan, demonstrasi dan pendampingan mengenai tatacara pengolahan telur menjadi abon. Data kuesioner ditabulasikan kemudian di analisa dalam membandingkan hasil akumulasi skor pre-test dengan skor post-test disertai dengan catatan observasi langsung ketika melakukan pendampingan. Hasil: Mendapatkan peningkatan jumlah peserta yang memiliki pengetahuan tentang anemia dalam kategori baik dari sebelum penyuluhan sebanyak 5 orang (13.5%) menjadi sebanyak 20 orang (54.1%). Terdapat juga peningkatan jumlah peserta yang memiliki ketrampilan dalam mengolah telur menjadi abon dari sebelum penyuluhan sebanyak 10 orang (27.0%) menjadi sebanyak 20 orang (94.6%). Simpulan: Kegiatan penyuluhan peningkatan pengetahuan tentang anemia dengan memberikan kemampuan berupa ketrampilan pengolahan makanan memiliki pengaruh yang sangat positif terhadap peningkatan pemahaman para kader dalam upaya pencegahan anemia dan stunting. Saran: Kepada para kader dapat melanjutkan kegiatan ini bersama dengan mitra dan koordinasi dengan tim PKM dalam upaya bersama pencegahan anemia pada 8000 HPK dan stunting.